KINERJA BALAI PENYULUHAN PERTANIAN NAPABALANO DALAM USAHATANI JAGUNG DI DESA PENTIRO KECAMATAN NAPABALANO KABUPATEN MUNA - Siti Ramlan; Usman Rianse; Salahuddin Salahuddin; Mardin Mardin (Universitas Halu Oleo, 2023)
This study aims to determine the level of performance of the Napabalano Agricultural Extension Center in Corn Farming in Pentiro Village, Napabalano District. The location of this research was determined purposively or intentionally based on the consideration that the Agricultural Extension Center (BPP) in Napabalano District is still active and is still running well in accordance with the program that has been prepared and is one of the designated villages so that the agricultural sector can improve welfare, especially for corn farmers. The number of respondents was 22 farmers who were determined using the census method. Data were analyzed using the class interval formula. The results showed that the performance of the Napabalano Agricultural Extension Center was in a fairly good category with a score of 60.954 as seen from the level of responsiveness, service quality and responsibility.